Russian Revisionism as a Challenge to the International Order - Parfinenko, Anatoliy; Парфіненко, Анатолій Юрійович (Institute of International Relations of Taras Shevchenko National University of Kyiv, 2023)
The article is devoted to highlighting geopolitical ambitions of Russian revisionism to build a multipolar world, which should replace the modern liberal international order of the Western model. The focus is on revealing ideological foundations of the foreign policy doctrine of Russian revisionism. The historical and political conditions of formation and the main parameters of modern Russian revisionism – geopolitical, spiritual-moral, historical-mythological – have been clarified and are considered against the background of Russia's historical aspiration for hegemony in Eurasia. The research is based on content analysis of public speeches and publications of Russian statesmen, ideologists and supporters of the Putin regime, which allows to determine the ideological basis of the revisionist course of the Kremlin, to establish declared and hidden motives of Russian aggression against Ukraine and the liberal international order. It is argued that the Russian invasion of Ukraine is an integral part of the strategy of building a multipolar world order, which involves establishing Russia as a civilizational pole, where the Kremlin projects power within the Russian sphere of influence. It is concluded that Russian revisionism poses an existential threat not only to Ukrainian independence and the countries of the post-Soviet space, but also to democratic institutions and values that define the liberal international order.
Російський ревізіонізм як виклик міжнародному порядку
Стаття присвячена висвітленню геополітичних амбіцій російського ревізіонізму щодо побудови багатополярного світу, який має витіснити сучасний ліберальний міжнародний порядок західного зразка. В центрі уваги розкриття ідеологічних основ зовнішньополітичної доктрини російського ревізіонізму. З’ясовано історико-політичні умови формування та основні параметри сучасного російського ревізіонізму – геополітичний, духовно-моральний, історико-міфологічний, які розглядаються на тлі історичного прагнення Росії до гегемонії в Євразії. Дослідження спирається на контент-аналіз публічних виступів та публікацій російських державних діячів, ідеологів та прибічників путінського режиму, що дозволяє визначити концептуально-ідеологічну основу ревізіоністського курсу Кремля, встановити декларовані та приховані мотиви російської агресії проти України та ліберального міжнародного порядку. Стверджується, що російське вторгнення в Україну є складовою частиною стратегії побудови багатополярного світового порядку, що передбачає утвердження за Росією статусу цивілізаційного полюсу, де Кремль здійснює проєкцію сили у межах російської сфери впливу. Робиться висновок, що російський ревізіонізм становить екзистенційну загрозу не тільки українській незалежності та країнам пострадянського простору, а й демократичним інститутам та цінностям, які визначають ліберальний міжнародний порядок.
Keywords: Russian revisionism; International order; Geopolitics; War in Ukraine; Post-Soviet space; European security